Pelatihan Publikasi Karya Ilmiah di Jurnal Ilmiah berbasis TIK bagi Guru Kelas - Dina Mardiana; Simpun Simpun; Kuswari Kuswari; Ichyatul Afrom; Kristiani Natalina; Sapriline Sapriline; Femmy Femmy (IKIP PGRI Bojonegoro, 2023)
ABSTRACTThe Community Empowerment Program (PPM) is one of the schemes in community service (PKM) activitiy carried out by the FKIP Lecturer Team from Palangka Raya University (UPR). This PKM-PPM activity was carried out for 30 classroom-teachers in Central Kalimantan Province through training and mentoring in an online workshop by a virtual zoom cloud meeting. The purpose of this PKM-PPM activity is to support the human resource excellence of classroom-teachers in terms of their competence to write scientific papers known as Classroom Action Research (PTK) and how to publish those papers in ICT-Based Scientific Journals or OJS. The training and mentoring method used was an integrated direct instruction-communicative approach which was held in July 2023. The science and technology provided through the implementation of this PKM-PPM activity can increase the knowledge and skill of classroom-teachers. This improvement is shown through the ability to compile scientific papers resulting from PTK reports and to submit those manuscripts to OJS-based scientific journals. This is also evidenced by the attainment of evaluation results on classroom-teacher activity and performance (during training and mentoring), in which it was shown by the score of 82 on-average with a completeness percentage of 91%. Thus it can be concluded that the PKM-PPM activity that has been carried out by the Lecturer Team from FKIP of Palangka Raya University in 2023 have succeeded.Keywords: publications, scientific papers, scientific journals, class teachers ABSTRAKProgram Pemberdayaan Masyarakat (PPM) merupakan salah satu skim dalam kegiatan pengabdian kepada masyarakat yang dilaksanakan oleh Tim Dosen FKIP dari Universitas Palangka Raya (UPR). Kegiatan PKM-PPM ini dilaksanakan kepada 30 orang guru kelas di Provinsi Kalimantan Tengah melalui pelatihan dan pendampingan berbentuk workshop secara daring dalam virtual zoom cloud meeting. Tujuan kegiatan PKM-PPM ini untuk mendukung keunggulan SDM Guru Kelas dalam hal kompetensi penulisan karya ilmiah berbentuk PTK dan cara mempublikasikannya di Jurnal Ilmiah Berbasis TIK atau OJS. Metode pelatihan dan pendampingan menggunakan pendekatan terpadu direct instruction-komunikatif yang dilaksanakan di bulan Juli tahun 2023 ini. Ipteks yang diberikan melalui pelaksanaan kegiatan PKM-PPM ini dapat meningkatkan pengetahuan dan keterampilan guru kelas. Peningkatan tersebut ditunjukkan melalui kemampuan menyusun artikel ilmiah hasil laporan PTK dan mengirimkan naskah artikel ilmiahnya tersebut ke jurnal ilmiah berbasis OJS. Hal tersebut juga dibuktikan dengan perolehan nilai hasil evaluasi terhadap aktivitas dan kinerja guru kelas (saat pelatihan dan pendampingan), yakni rata-rata 82 dengan persentase ketuntasan 91%. Dengan demikian dapat disimpulkan kegiatan PKM-PPM yang telah dilaksanakan Tim Dosen dari FKIP Universitas Palangka Raya pada tahun 2023 ini telah terlaksana dengan baik.Kata Kunci: publikasi, karya ilmiah, jurnal ilmiah, guru kelas